Can radiological results be surrogate markers of functional outcome in distal radial extra-articular fractures? - Kumar, Skand (Springer-Verlag, 2007)
The purpose of this study was to evaluate the relationship between radiological and functional results in patients with extra-articular fractures of the distal radius. We conducted a prospective study of radiological and functional assessment in 95 consecutively selected extra-articular distal radius fractures. There were two patient groups: more than 60 and less than 60 years of age. The final fracture union radiographs were analysed for their functional outcome using the Michigan Hand Outcomes Questionnaire (MHQ) and the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire. In patients with acceptable radiological results, 62% (MHQ group) and 72% (DASH group) of patients had satisfactory functional outcome. Analysing patients with satisfactory functional results, 56% (MHQ group) and 59% (DASH group) had satisfactory radiological results. There was a higher proportion of patients with better functional results, despite poor radiological results, in both of the age groups. There was a statistically significant correlation between satisfactory radial tilt and functional outcome in the younger patients. In the older age group, patients with satisfactory radiological results had satisfactory functional outcome (p < 0.05). However, in the older age group, satisfactory functional results were achieved, despite unsatisfactory radiological results.